Pengaruh Citra Merek dan Promosi Terhadap Keputusan Pembelian Sepeda Motor Yamaha di Mayjend Sungkono Surabaya - Riza Yunizar; Aminah Aminah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The goal of this study was to examine the influence of brand image and promotion on the purchase decisions of Yamaha motorcycles at Mayjend Sungkono Surabaya. Surabaya residents who own or ride Yamaha motorcycles are the target audience for this study. This study employs a non-probability sampling method with a purposive sampling technique, in which the researcher selects research samples based on predetermined characteristics and characteristics. A total of 65 people were included in the study. PLS is the data analysis method employed. Purchase decisions are influenced by brand image and promotions, which have been found to have a positive and significant impact on them in previous studies. Keywords: Brand Image; Promotion; Buying decision.